Calculation and Analysis of Transient E-Field Distribution of 110kV Dry Type Transformer Under Lightning Impulse. (November 2020) - Zhou, Junfeng; Wang, Shuo; Peng, Chong; Wang, Ning; Wang, Kang; Zhu, Tiantong
Abstract: The 110kV dry type epoxy casting transformer had the characteristics of high voltage grade, great difficulty and uncertainty in research. Especially in the field strength control under lightning impulse, higher requirements were put forward for its insulation structure design. In this paper, an equivalent circuit model was built based on the heap winding structure, and the voltage distribution of winding nodes under lightning impulse was calculated. According to the actual drawing, a two-dimensional transformer model was established, and the E-field distribution of transformer under lightning impulse was obtained by simulation. The results showed that the maximum field strength at sampling point 1 was 4.1kV/mm, appearing around 65μs and 157μs. From the simulation results, the insulation performance of the pile winding did not meet the safety requirements. The research results in this paper could provide an important basis for the design of 110kV dry type transformer and technical support for the product development and safe operation of large capacity dry type transformer.